2013
DOI: 10.1093/cid/cit207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smoking on Non-AIDS-Related Morbidity in HIV-Infected Patients

Abstract: Tobacco smoking has many adverse health consequences. Patients with human immunodeficiency virus (HIV) infection smoke at very high rates, and many of the comorbidities associated with smoking in the general population are more prevalent in this population. It is likely that a combination of higher smoking rates along with an altered response to cigarette smoke throughout the body in persons with HIV infection leads to increased rates of the known conditions related to smoking. Several AIDS-defining conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 102 publications
1
60
0
Order By: Relevance
“…7,9,48,49 Studies show an increase in COPD in this population, and as in the general population, this number is likely under-reported due to lack of screening and in HIV infected patients, a historical emphasis of HIV treatment as a priority over testing and management of chronic diseases. 2,5,50 In our pilot study of a COPD screening strategy in an HIV clinic, we found that 12% of those completing spirometry had evidence of previously undiagnosed obstructive lung disease, revealing clear deficits in the recognition of pulmonary disease in this population.…”
Section: Discussionmentioning
confidence: 90%
“…7,9,48,49 Studies show an increase in COPD in this population, and as in the general population, this number is likely under-reported due to lack of screening and in HIV infected patients, a historical emphasis of HIV treatment as a priority over testing and management of chronic diseases. 2,5,50 In our pilot study of a COPD screening strategy in an HIV clinic, we found that 12% of those completing spirometry had evidence of previously undiagnosed obstructive lung disease, revealing clear deficits in the recognition of pulmonary disease in this population.…”
Section: Discussionmentioning
confidence: 90%
“…Smoking also appears to have a compounding effect on chronic systemic inflammation associated with HIV, and this exaggerated inflammation may increase the risk for chronic illnesses such as chronic obstructive pulmonary disease, atherosclerotic disease, and others. 27 …”
Section: Smoking-related Morbidity and Mortality Among Plwhamentioning
confidence: 99%
“…Youth are also characterized by higher rates of sexual risk behaviors (Eaton et al, 2012) and poor medication adherence (Tanney et al, 2010); exacerbation of these risk behaviors by substance use has implications for HIV prevention and treatment outcome. In addition, tobacco use is higher among individuals with HIV than in the general population (Webb et al, 2007), and is an important contributor to non-AIDS-defining as well as AIDS-defining illness and mortality in this population (Helleberg et al, 2013; Shirley et al, 2013). Accurate assessment of substance use among youth with HIV has great importance for research on HIV treatment and outcomes as well as for clinical care.…”
Section: Introductionmentioning
confidence: 99%